Malouf Syndrome with Hypergonadotropic Hypogonadism and Cardiomyopathy: Two-Case Report and Literature Review - Dilek Benk Şilfeler; Atilla Karateke; Raziye Keskin Kurt; Özgür Aldemir; Alper Buğra Nacar; Ali Baloğlu (Case Reports in Obstetrics and Gynecology)
Malouf syndrome is a very rarely encountered syndrome which was first diagnosed in 1985 upon the examination of two sisters, with findings of hypergonadotropic hypogonadism, dilated cardiomyopathy, blepharoptosis, and broad nasal base. Later on, Narahara diagnosed another sporadic case with the same findings. A survey of relevant literature leads us to three women cases in total. Here we present two cases of Malouf syndrome and literature review.